Some observations of student teaching programs in selected American universities - Tablante, Isabel L.
It is worthwhile to examine and improve program to make them relevant to the changing needs of the clients. There are many role models as there are alternative implementation mechanisms. The description of the programs may suggest some ideas for improving or revising existing student teaching programs in teacher education institutions.
Keywords: Student teaching -- United States; Student teachers -- United States; Teachers -- Training of -- United States